2007
DOI: 10.1007/s11745-007-3134-5
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Standardize Ethics Guiding the Peer Review Process?

Abstract: While most scientific journals have well defined ethics requirements for authors, very few journals explicitly specify the ethics standards that govern the actions of editors, editorial board members, and reviewers. We believe it is time to create a standardized policy for all medical and scientific journals that guides the ethical conduct of all stakeholders in the peer review process.In their recent article, James et al.(1) comment on the role of medical journals and the peer review process in the assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Secondly, our results confirm the need to improve ethical conduct and reputational motives for referees so as to maximize their reliability and commitment (e.g., Bosetti & Toscano, 2008). In reality, we know that reviewing is not at the top of the list for academic reputation.…”
Section: Discussionsupporting
confidence: 70%
“…Secondly, our results confirm the need to improve ethical conduct and reputational motives for referees so as to maximize their reliability and commitment (e.g., Bosetti & Toscano, 2008). In reality, we know that reviewing is not at the top of the list for academic reputation.…”
Section: Discussionsupporting
confidence: 70%
“…The type of manuscripts published in any given journal is a function of the journal's editorial focus, the editor-in-chief, the editorial board, the publisher's staff, the reviewer pool, institutional affiliations, and the readers. Although bias has been reported at the editor level and among reviewers, [25][26][27][28][29][30][31] both groups lack the resources to adequately assess COI. Neither group has the resources to check the veracity of reported conflicts of interest nor do they have the authority to manage COIs if present, which raises the question of whether editors and reviewers are the appropriate individuals to police publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Bosetti and Toscano cite an analysis of the Vioxx debacle by James et al as one of the most egregious cases of financial conflicts of interest in the history of the peer-review process that calls out for more stringent ethics standards. 74 James et al blame pharmaceutical company sales and marketing practices and uncritical reviewers at the New England Journal of Medicine of Merck-sponsored research that dismissed concerns of cardiovascular issues. 75 Spielmans et al examined the clinical trials on duloxetine, a treatment for depression, 76 to see how data were reported across 43 analyses, and found that in 88% of them at least one author was employed by a manufacturer of the drug and that six clinical trials were part of 20 or more separately published analyses.…”
Section: Conflicts Of Interestmentioning
confidence: 99%